Canadian Healthcare System and Individuals with Severe Mental Disorders During Coronavirus Disease 2019: Challenges and Unmet Needs. Issue 1 (18th October 2022) - Lui, Leanna M W; McIntyre, Roger S
Abstract: The Coronavirus Disease 2019 (COVID-19) pandemic is a syndemic of viral infection and mental health adversity. The pandemic has exacerbated inequalities of access to care in vulnerable populations within the Canadian mental healthcare system. Primary care services are first-line health services in Canada, and are necessary to access specialized services. However, as a result of the limited availability of primary health services, and subsequently, specialized providers (eg, psychiatrists), the demand for these services outweigh the supply. Hitherto, timely access to appropriate services has been cited as a common challenge in Canada as a result of limitations as it relates to resources and in-person activities and support services. While there has been an increase in virtual care opportunities, concerns have been raised with respect to the digital divide. Moreover, while individuals with serious mental illness (SMI) and psychosis are at an increased risk for hospitalization and death from COVID-19, testing and vaccination services have not been prioritized for this population. Taken together, increased funding for mental health service delivery should be emphasized especially for individuals with SMI. There should also be a focus on increased collaboration among individuals with lived experience and health care providers to ensure future policies are developed specifically for this population. Addressing the social determinants of health and prioritizing a continuum of care across various stakeholders may lead to strong integration of care both during and after the pandemic.